Estudo do comprometimento e motivação de funcionários terceirizados como processo de melhoria da gestão institucional na UFC - Diógenes, Sandra Helena do Areal Barra (2013)
Outsourcing is becoming increasingly evident in everyday public institutions in Brazil, and should be considered as an administrative tool of the present day, in which we observe strategic organizational changes. Strategic management of public administration establishes ways that seek to achieve success, through the optimization of time, agility of processes, reduce of costs, improvement of the quality of services, making it more dynamic, flexible and efficient. Thus, the study aims to investigate the factors of motivation and organizational commitment of these employees in the cleaning, hygiene and maintenance of the internal areas and general services of the UFC. Theorists and researchers have contributed to the brief literature review, highlighting the contribution of Meyer and Allen (1990, 1991, 1997), Siqueira (2001, 2004, 2008) and Vroom (1964, 1997) on motivation, organizational commitment and Outsourcing. This research is characterized as a descriptive study, qualitative and quantitative, regarding the goals. Concerning data collection, it consists of a literature review and a case study, type ex-post facto, because the data is observed in comparison of the facts detected in the unit under test. As a research instrument, the questionnaire was used, which was applied in a purposive sample consisting of 233 respondents. The data collected revealed that the lack of reward and opportunity condition is the predominant motivation and commitment of outsourced employees in the institution. It’s possible to conclude that, if the company and the UFC given the respondent quality material, plus good performance of their supervisors, there will be a greater involvement which will influence the motivation and commitment of employees.